The Relationships between Web Design, Reliability, Privacy, Service Quality, and Purchase Intention of Customers at E-commerce Business - Johan, Kevin; Samantha, Wella; Tandean, Maria J.; Sihombing, Sabrina (SBM ITB, 2020)
Abstract. Of the many e-commerce players in Indonesia, Zalora is one of the main online shopping. However, there is a decrease rank in Zalora where in 2018 Zalora was ranked 7th but dropped to 10th in 2019. Therefore, the research aims to predict purchase intentions through Zalora which are influenced by perceptions of web design, perceptions of reliability, privacy, and customer service. This research uses quantitative methods, and data collection techniques are carried out by distributing questionnaires to the non-probability sampling method. Samples taken were 40 respondents for preliminary tests and 200 respondents for actual tests, with the criteria of ever shopping at Zalora. Data obtained in the preliminary study were tested by testing the reliability and validity. Data obtained from actual research is tested by testing the reliability, validity, and classical assumption tests. Next, the data are analyzed with Structural Equation Modeling (SEM) to test hypotheses and draw conclusions. Thus, the results show that the nine research hypotheses are supported. This study also provides theoretical implications, managerial implications, and recommendations for further research.Keywords: Purchase intention, web design, reliability, privacy, customer serviceAbstrak. Dari sekian banyak pemain e-commerce di Indonesia, Zalora adalah salah satu belanja online utama. Namun, ada penurunan peringkat di Zalora di mana pada 2018 Zalora berada di peringkat 7 tetapi turun ke 10 di 2019. Oleh karena itu, penelitian ini bertujuan untuk memprediksi niat beli melalui Zalora yang dipengaruhi oleh persepsi desain web, persepsi keandalan, privasi, dan pelayanan pelanggan. Penelitian ini menggunakan metode kuantitatif, dan teknik pengumpulan data dilakukan dengan menyebarkan kuesioner dengan metode pengambilan sampel non-probabilitas. Sampel yang diambil adalah 40 responden untuk tes pendahuluan dan 200 responden untuk tes aktual, dengan kriteria pernah berbelanja di Zalora. Data yang diperoleh dalam studi pendahuluan diuji dengan menguji reliabilitas dan validitas. Data yang diperoleh dari penelitian aktual diuji dengan menguji reliabilitas, validitas, dan uji asumsi klasik. Selanjutnya, data dianalisis dengan Structural Equation Modeling (SEM) untuk menguji hipotesis dan menarik kesimpulan. Dengan demikian, hasilnya menunjukkan bahwa sembilan hipotesis penelitian didukung. Studi ini juga memberikan implikasi teoritis, implikasi manajerial, dan rekomendasi untuk penelitian lebih lanjut.Kata kunci: Niat membeli, disain web, keandalan, privasi, layanan konsumen